How Important is Marrying Within the Faith? Conversations with Canadian Jewish Singles - Libby Bear; Randal F. Schnoor (Canadian Jewish Studies)
This article explores the factors that Jewish singles consider when selecting an intimate partner. It assesses the degree to which they take into account whether potential mates are Jewish. Using data collected through in-depth interviews with Canadian Jewish singles, the study seeks to shed light on the values that guide individuals in their decisions regarding relationships and marriage, as well as the challenges they encounter in pursuing those values. The findings reveal that although attitudes and perceptions towards endogamy change as people age, endogamy and Jewish particularism are still important considerations for Jewish adults. Situating this finding in the larger context of debates around Jewish continuity, the article argues that these patterns help to mitigate assimilation in the Canadian Jewish community.